CONGWAYNDUT: REFLEKSI FUNGSIONALISME STRUKTURAL SENI PERTUNJUKAN YANG MELINTAS BATAS - Wrahatnala, bondet (Institut Seni Indoensia Surakarta, 2020)
Abstract This paper positions itself as a study that portrays the Keroncong Wayang Gendut (Congwayndut) performance, as performance art that reflects structural functionalism. Because Congwayndut explicitly contained aspects of structural functionalism. In this paper, Congwayndut is positioned as an organism that has a structure and functions socially and culturally. Congwayndut is one of the many performing arts groups capable of interpreting traditional art in contemporary, meaning that it responds to the millennial generation with the construction of traditional performances, namely shadow puppet art. . Congwayndut has an important role in the development process or as a performance art model that accommodates other art disciplines, including music, wayang, theater, script, visuals, dramaturgy, which are combined as a typical Indonesian performance art prototype. Therefore, the structural-functional point of view emerged, as a step to explain to the public about the cultural phenomena experienced by Congwayndut. Structural functionalism was born as a reaction against the theory of evolution. If evolutionary studies aim to establish the stages of human cultural development, then structural-functionalism studies aim to build a social system, or social structure, through the study of the functioning patterns of relations between individuals, between groups. -groups, or between social institutions in a society, at a certain period of time. Keywords: Congwayndut, Cross-Border Performing Arts, Structural Functionalism Abstrak Tulisan ini, memposisikan diri sebagai kajian yang memotret pertunjukan Keroncong Wayang Gendut (Congwayndut), sebagai seni pertunjukan yang merefelksikan fungsionalisme struktural. Karena di dalam Congwayndut secara eksplisit terkandung aspek fungsionalisme struktural. Congwayndut di dalam tulisan ini diposisikan sebagai organisme yang memiliki struktur, dan memiliki fungsi secara sosial budaya.Congwayndut adalah satu satu dari sekian banyak kelompok seni pertunjukan, yang mampu menafsir seni tradisi secara kekinian, artinya merespon generasi milenial dengan konstruksi pertunjukan tradisi yakni kesenian wayang kulit. Congwayndut memiliki peran penting dalam proses pengembangan atau sebagi model seni pertunjukan yang mengakomodir disiplin seni yang lain, ada musik, wayang, teater, naskah, rupa, dramaturgi, yang dijadikan satu sebagai purwarupa seni pertunjukan yang khas Indonesia. Oleh sebab itu lah sudut pandang struktural fungsional muncul, sebagai langkah untuk menjelaskan kepada publik, tentang gejala fenomena budaya yang dialami oleh Congwayndut. Fungsionalisme struktural lahir sebagai reaksi terhadap teori evolusi. Jika tujuan dari kajian-kajian evolusi adalah untuk membangun tingkat-tingkat perkembangan budaya manusia, maka tujuan dari kajian-kajian fungsionalisme struktural adalah untuk membangun suatu sistem sosial, atau struktur sosial, melalui pengajian terhadap pola hubungan yang berfungsi antara individu-individu, antara kelompok-kelompok, atau antara institusi-institusi sosial di dalam suatu masyarakat, pada suatu kurun masa tertentu. Kata Kunci : Congwayndut, Seni Pertunjukan Lintas Batas, Fungsionalisme Struktural